2001
DOI: 10.4269/ajtmh.2001.65.167
|View full text |Cite
|
Sign up to set email alerts
|

Rapid reappearance of Plasmodium falciparum after drug treatment among Senegalese adults exposed to moderate seasonal transmission.

Abstract: Abstract. To investigate the relationship between the entomologic inoculation rate (EIR) and time to reappearance of malaria parasites after radical treatment under moderate seasonal transmission conditions, a study was undertaken in a mesoendemic area of Senegal where malaria transmission is concentrated over an annual three-month period and averages 12 infective bites per person per year. A three-day course of quinine was administered to 48 asymptomatic adults between 19 and 66 years of age. Malaria transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…In our study, we utilise field data on malaria infection dynamics after a short treatment course in a holoendemic region of Kenya. The estimated P. falciparum infection rates are extremely high, especially amongst young children, but consistent with the high entomological infection rates measured in this area [29]and with the blood-stage infection rates previously observed by others in similar studies [30], [31]. The prior treatment of patients gives an ideal opportunity to study malaria incidence in the absence of recrudesence from prior infection.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, we utilise field data on malaria infection dynamics after a short treatment course in a holoendemic region of Kenya. The estimated P. falciparum infection rates are extremely high, especially amongst young children, but consistent with the high entomological infection rates measured in this area [29]and with the blood-stage infection rates previously observed by others in similar studies [30], [31]. The prior treatment of patients gives an ideal opportunity to study malaria incidence in the absence of recrudesence from prior infection.…”
Section: Discussionsupporting
confidence: 88%
“…However, there is in vitro and in vivo evidence of CQ‐resistant Plasmodium falciparum with consequential high rates (up to 50%) of treatment failure (Pradines et al. 1996; Sokhna et al. 1997, 2001a,b; Brasseur et al.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies carried out in low-, medium-, and high-transmission areas have measured the time required for Plasmodium parasites to reappear in the blood of individuals after parasitemia has been cleared with blood-stagespecific antimalarial compounds (14,15,21,30,(44)(45)(46)(47). Interestingly, these and other modeling studies have revealed a discrepancy between the estimated number of infective bites per human per time unit (i.e., the EIR) and the resulting force of infection (FOI; i.e., the rate of new blood-stage infections) (16,33).…”
Section: Induction Of Type I Ifn and Ifn-␥ By A First P Berghei Livementioning
confidence: 99%